Negative electrode material, preparation method, secondary battery and electrical equipment

By forming a coating layer with primary amino groups and catechol groups on the surface of silicon-based negative electrode materials, the problem of battery capacity attenuation and cycle life reduction caused by volume expansion of silicon-based materials in lithium-ion batteries is solved, achieving It has stronger mechanical strength and self-healing function, and improves the cycle performance of the battery.

CN116632172BActive Publication Date: 2025-01-21SVOLT ENERGY TECHNOLOGY CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310771765.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-28
Publication Date
2025-01-21
Estimated Expiration
2043-06-28

AI Technical Summary

Technical Problem

The silicon-based negative electrode material causes the cracking, powdering and electrolyte membrane rupture during the charging and discharging cycle of lithium-ion batteries, resulting in the attenuation of battery capacity and reduced cycle life.

Method used

A negative electrode material with a coating layer structure is used. The coating layer is formed by covalently connecting a first substance with a primary amino group (such as polyethylenimine) and a second substance containing a catechol group to form a more stable material. Polymer skeleton with strong mechanical strength and self-healing function.

Benefits of technology

It effectively suppresses the volume expansion of silicon-based materials during the process of deintercalating lithium, improves the long-term cycle performance and mechanical strength of the battery, and extends the cycle life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present application discloses a negative electrode material, a preparation method, a secondary battery and an electrical device. The negative electrode material of the present application includes an active material and a coating layer coated on the surface of the active material, the coating layer includes a first substance, the first substance has a primary amino group; the primary amino group in the first substance is at least partially connected to a second substance; the second substance includes a catechol group. The preparation method of the present application includes dispersing the second substance in a solvent to obtain a first slurry; adding the active material to the first slurry to obtain a second slurry; adding the first substance to the second slurry to obtain a third slurry; the third slurry is spray-dried under an inert atmosphere to obtain a negative electrode material. The present application coats the active material with a coating layer, which can inhibit the volume expansion of the active material during the battery cycle, and the negative electrode material has a stronger mechanical strength, which improves the long-term cycle performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a negative electrode material, a preparation method, a secondary battery and an electrical device. Background Art

[0002] Graphite is a common negative electrode material for lithium-ion batteries, but its low specific capacity limits its application as a high-energy density negative electrode material. Silicon-based negative electrode materials have ultra-high theoretical specific capacity, but the silicon-based materials are accompanied by huge volume expansion during the lithium insertion process. Therefore, during the charge and discharge cycle, as the lithium insertion and de-lithiation proceed, the internal stress generated by the huge volume expansion of the silicon-based material particles will cause the active particles to crack, break, or even pulverize, and the solid electrolyte (SEI) film on the surface of the active particles to continuously break and regenerate, resulting in the failure of active substances and loss of active lithium, rapid decay of battery capacity, and reduced battery cycle life. Summary of the invention

[0003] The purpose of this application is to provide a negative electrode material, a preparation method, a secondary battery and an electrical device that can solve the above-mentioned technical problems.

[0004] The embodiment of the present application provides a negative electrode material, including an active material and a coating layer coated on the surface of the active material, wherein the coating layer includes a first substance, the first substance has a primary amino group; the primary amino group is at least partially connected to a second substance;

[0005] The second substance has a catechol group.

[0006] In some embodiments, the catechol groups in the second substance are at least partially linked to a third substance, and the third substance includes one or more of 1,4-phenylenediboronic acid, 1,3-phenylenediboronic acid, and boric acid.

[0007] In some embodiments, the active material includes one or more of silicon, silicon-carbon composites, silicon-oxygen compounds, silicon-nitrogen compounds, and silicon alloys.

[0008] In some embodiments, the first substance comprises polyethyleneimine.

[0009] In some embodiments, the second substance includes one or more of catechol, gallic acid, tannic acid, quercetin, ellagic acid, chlorogenic acid, protocatechuic acid, and epicatechin gallate.

[0010] In some embodiments, the mass ratio of the coating layer to the active material is 1:(40-200).

[0011] In some embodiments, the particle size of the active material is 100 nm to 20 μm.

[0012] In some embodiments, the coating layer has a thickness of 100 nm to 900 nm.

[0013] In some embodiments, the molecular weight of the first substance is 8000-20000 Da.

[0014] In some embodiments, the mass ratio of the first substance to the second substance is (2-15):(2-10).

[0015] In some embodiments, the mass ratio of the first substance, the second substance and the third substance is (2-15):(2-10):1.

[0016] Accordingly, an embodiment of the present application provides a method for preparing the above-mentioned negative electrode material, comprising the following steps:

[0017] dispersing the second substance in a solvent to obtain a first slurry;

[0018] adding the active material to the first slurry to obtain a second slurry;

[0019] adding the first substance to the second slurry to obtain a third slurry;

[0020] The third slurry is spray-dried under an inert atmosphere to obtain the negative electrode material.

[0021] Accordingly, an embodiment of the present application provides a secondary battery, including a negative electrode plate, wherein the negative electrode plate includes the negative electrode material described above or the negative electrode material prepared by the method for preparing the negative electrode material described above.

[0022] Accordingly, an embodiment of the present application provides an electrical device including the above-mentioned secondary battery.

[0023] The beneficial effects of the present application are as follows: compared with the prior art, the present application provides a negative electrode material, a preparation method, a secondary battery and an electrical device. The negative electrode material of the present application includes: an active material and a coating layer coated on the surface of the active material, the coating layer includes a first substance, the first substance has a primary amino group; the primary amino group in the first substance is at least partially bonded to the second substance; the second substance includes a catechol group. The negative electrode material of the present application has stronger mechanical strength, can better inhibit the volume expansion of the silicon-based material during the lithium extraction process, and improve the long-term cycle performance of the battery. DETAILED DESCRIPTION

[0024] The technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work belong to the scope of protection of the present application. In addition, in the description of the present application, the term "including" means "including but not limited to". The terms first, second, third, etc. are used only as labels, and no numerical requirements or order are imposed. Various embodiments of the present application may exist in the form of a range; it should be understood that the description in the form of a range is only for convenience and simplicity, and should not be understood as a hard limit to the scope of the present application; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single values ​​within the range. For example, it should be considered that the range description from 1 to 6 has specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the numbered range, such as 1, 2, 3, 4, 5 and 6, which are applicable regardless of the range. Additionally, whenever a numerical range is indicated herein, it is meant to include any cited numeral (fractional or integral) within the indicated range.

[0025] During the charge and discharge cycle of the negative electrode active material, as lithium insertion and delithiation proceed, the internal stress generated by the volume expansion of the particles leads to failure of the active material and loss of active lithium. The prior art often uses polymers as coating layers to inhibit their expansion, but if the main structure of the polymer is relatively rigid and lacks flexibility and self-healing properties, the coating polymer has poor fatigue resistance and cannot meet the long-term cycle requirements of silicon-based materials. In view of this, the embodiments of the present application provide a negative electrode material that can effectively improve the volume expansion of the negative electrode material and improve the long-term cycle performance of the battery. In some embodiments of the present application, the negative electrode material includes an active material and a coating layer coated on the surface of the active material, the coating layer includes a first substance, the first substance has a primary amino group; the primary amino group is at least partially connected to a second substance; the second substance has a catechol group.

[0026] The term "connection" used in this application refers to a chemical bond between atoms used to connect or interact with each other, such as an ionic bond, a covalent bond, a coordination bond, and the like.

[0027] In the present application, the polymer having a primary amino group undergoes a Michael addition reaction or a Schiff base formation reaction with the second substance containing a catechol group, and the first substance and the second substance are connected by a covalent bond to form a polymer skeleton that encapsulates the active substance. The polymer has stronger mechanical strength and can better inhibit the volume expansion of the active material during lithium insertion and extraction.

[0028] In some embodiments, the first substance includes polyethyleneimine, which has strong toughness and can better suppress the volume expansion of the active material.

[0029] In some embodiments, the molecular weight of the first substance is 8000-20000Da. In some embodiments, the molecular weight of the first substance refers to the weight-average molecular weight (Mw), such as when the molecular weight of the first substance is 8000, 9000, 10000, 11000, 12000, 13000, 14000, 15000, 16000, 17000, 18000, 19000, 20000, any value or a range consisting of any two values. The molecular weight of the first substance of the present application is within this range, which can better improve the coating performance of the coating layer.

[0030] In some embodiments, the second substance includes one or more of catechol, gallic acid, tannic acid, quercetin, ellagic acid, chlorogenic acid, protocatechuic acid, and epicatechin gallate. In the present application, the second substance containing a catechol group is connected by the first substance to further improve the toughness of the polymer and increase the inhibitory effect of the polymer on the volume expansion of the active substance.

[0031] In some embodiments, the mass ratio of the first substance to the second substance is (2-15): (2-10). For example, the mass ratio of the first substance to the second substance is (2-8): (2-9), (2-8): (2-6), (3-8): (2-6). In some embodiments, the mass ratio of the first substance to the second substance is any value of 1:1, 1:2, 1:3, 1:4, 1:5, 7.5:1, 7:1, 6:1, 5:1, 4:1, 3:1, 2:1, 5:3, 4:3, or a range consisting of any two values. When the mass ratio of the first substance and the second substance of the present application is within this range, the toughness of the polymer can be improved, the coating performance of the polymer on the active material can be increased, and the cycle stability of the battery can be improved.

[0032] In some embodiments, the catechol groups in the second substance are at least partially linked to a third substance, and the third substance includes one or more of 1,4-phenylenediboronic acid, 1,3-phenylenediboronic acid, and boric acid.

[0033] The present application introduces boric acid into the polymer to form a reversible borate bond with the catechol structure, and forms a dynamic chemical cross-linking point inside the polymer. Since the borate bond is reversible, and there are a large number of hydrogen bonds, Π-Π interactions and coordination effects inside the polymer, when the active material particles are embedded with lithium and produce a large expansion stress, the coating layer can dissipate the stress through the fracture of dynamic borate bonds, hydrogen bonds and Π-Π interactions, and the borate bonds, hydrogen bonds and Π-Π interactions in the polymer can be re-formed after lithium removal, so that the coating layer has excellent fatigue resistance, thereby effectively maintaining the integrity of the silicon-based negative electrode material in the long-term cycle of the battery and improving the cycle performance of the battery.

[0034] In some embodiments, in the coating layer of the present application, hydrogen bonds between polyethyleneimine molecules, hydrogen bonds between polyethyleneimine and compounds containing catechol groups, π-π interactions between compounds containing catechol groups, and BN coordination between borate groups and polyethyleneimine make the coating layer have self-healing function, thereby improving the long-term cycle stability of the active material.

[0035] In some embodiments, the mass ratio of the first substance, the second substance and the third substance is (2-15): (2-10): 1. For example, the mass ratio of the first substance, the second substance and the third substance is (2-8): (2-9): 1, (2-8): (2-6): 1, (3-8): (2-6): 1. In some embodiments, the mass ratio of the first substance, the second substance and the third substance is any value of 2:2:1, 2:4:1, 2:5:1, 2:6:1, 2:10:1, 15:2:1, 10:2:1, 6:2:1, 4:2:1, or a range consisting of any two values. When the mass ratio of the first substance, the second substance and the third substance of the present application is within this range, the polymer has better fatigue resistance, thereby effectively maintaining the integrity of the active material during long-term battery cycling.

[0036] In some embodiments, the mass of the coating layer is based on the total mass of the first substance, the second substance, and the third substance.

[0037] In some embodiments, the active material includes one or more of silicon alone, silicon-carbon composites, silicon-oxygen compounds, silicon-nitrogen compounds, and silicon alloys.

[0038] In some embodiments, the mass ratio of the coating layer to the active material is 1:(40-200). For example, the mass ratio of the coating layer to the active material is any value of 1:40, 1:50, 1:60, 1:70, 1:80, 1:90, 1:100, 1:110, 1:120, 1:130, 1:140, 1:150, 1:160, 1:170, 1:180, 1:190, 1:200, or a range consisting of any two values. Alternatively, in some embodiments, based on the mass of the active material, the mass percentage (%) of the coating layer to the active material is 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, any value or a range consisting of any two values.

[0039] In some embodiments, the particle size of the active material is 100 nm to 20 μm. For example, in some embodiments, the particle size of the active material is any value of 100 nm, 200 nm, 500 nm, 1000 nm, 1.5 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 15 μm, 20 μm, or a range consisting of any two values.

[0040] In some embodiments, the thickness of the coating layer is 100nm to 900nm. For example, in some embodiments, the thickness (nm) of the coating layer is any value of 100, 200, 300, 400, 500, 600, 700, 800, 900 or a range consisting of any two values. The coating layer of the present application has a better coating effect within this range. When the coating layer is too thin, the coating is uneven, it is difficult to form a complete coating, the expansion inhibition effect of the active material is poor, the side reaction between the active material and the electrolyte is serious, and the cycle attenuation is serious. When the coating layer is too thick, the gram capacity of the active material is reduced, and the impedance of lithium ions penetrating the coating layer increases, polarization is serious, and the capacity decays quickly.

[0041] The embodiments of the present application further provide a method for preparing a negative electrode material, comprising the following steps:

[0042] dispersing the second substance in a solvent to obtain a first slurry;

[0043] adding active material to the first slurry to obtain a second slurry;

[0044] adding the first substance to the second slurry to obtain a third slurry;

[0045] The third slurry is spray-dried under an inert atmosphere to obtain a negative electrode material.

[0046] In some embodiments, a method for preparing a negative electrode material comprises the following steps:

[0047] Dispersing the second substance and the third substance in a solvent to obtain a first slurry;

[0048] adding active material to the first slurry to obtain a second slurry;

[0049] adding the first substance to the second slurry to obtain a third slurry;

[0050] The third slurry is spray-dried under an inert atmosphere to obtain a negative electrode material.

[0051] In some embodiments, the solvent includes water.

[0052] In some embodiments, the inert atmosphere refers to an inert non-oxidizing atmosphere, such as a nitrogen or argon atmosphere.

[0053] In some embodiments, the apparatus used for spray drying is a spray dryer.

[0054] An embodiment of the present application further provides a secondary battery, comprising a negative electrode plate, wherein the negative electrode plate comprises the above-mentioned negative electrode material or the negative electrode material prepared by the above-mentioned preparation method.

[0055] In some embodiments, the negative electrode plate further includes a negative electrode current collector, which may be a copper foil.

[0056] The secondary battery provided in the embodiment of the present application further comprises a positive electrode sheet, a separator and an electrolyte. In specific implementation, the positive electrode sheet, the negative electrode sheet, the separator and the electrolyte are assembled into a secondary battery.

[0057] In some embodiments, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on the positive electrode current collector. The positive electrode active material layer includes a positive electrode material, a conductive agent, and a binder. In specific implementation, the above-mentioned positive electrode material, the conductive agent, the binder, and the solvent are mixed evenly, and the positive electrode sheet is made through the processes of screening, coating, rolling, slitting, and cutting.

[0058] In some embodiments, the positive electrode material includes lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, lithium manganese iron phosphate, lithium nickel cobalt manganese oxide and the like.

[0059] In some embodiments, the type of conductive agent is not limited, and any known conductive agent can be used. Examples of conductive agents may include, but are not limited to, one or more of the following: natural graphite, artificial graphite, Super P conductive carbon black, acetylene black, needle coke, carbon nanotubes, graphene and other carbon materials. The above positive electrode conductive agents can be used alone or in any combination.

[0060] The type of binder used in the manufacture of the positive electrode active material layer is not particularly limited. In the case of the coating method, it can be any material that is soluble or dispersible in the liquid medium used in the manufacture of the electrode. The binder includes, but is not limited to, one or more of the following: polyethylene, polypropylene, polyvinylidene fluoride (PVDF), polytetrafluoroethylene, fluorinated polyvinylidene fluoride, etc. The above binders can be used alone or in any combination.

[0061] There is no restriction on the type of solvent used to form the positive electrode slurry, as long as it is a solvent that can dissolve or disperse the positive electrode active material, the conductive agent, and the binder. The solvent used to form the positive electrode slurry includes any one of an aqueous solvent and an organic solvent. Aqueous solvents include, but are not limited to, water, a mixed medium of alcohol and water, etc. Organic solvents include, but are not limited to, hexane, benzene, toluene, xylene, pyridine, acetone, tetrahydrofuran (THF), N-methylpyrrolidone (NMP), etc.

[0062] In some embodiments, the electrolyte includes a lithium salt, an organic solvent, and a film-forming additive.

[0063] In some embodiments, the lithium salt is selected from one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4) or lithium bis(fluorosulfonyl)imide (LiFSI). The mass percentage of the lithium salt in the electrolyte is 10% to 15%. For example, the mass percentage of the lithium salt in the electrolyte is 10%, 11%, 11.5%, 12%, 12.5%, 13%, 13.5%, 14%, 14.5%, 15%, or any range consisting of any two of the values.

[0064] In some embodiments, the organic solvent includes one or more of ethylene carbonate (EC), dimethyl carbonate (DMC), diethyl carbonate (DEC), and ethyl methyl carbonate (EMC).

[0065] In some embodiments, the film-forming additive is selected from chlorosulfonyl isocyanate (CSI) or fluoroethylene carbonate (FEC). The mass percentage of the film-forming additive in the electrolyte is 0.1% to 1%. For example, the mass percentage of the film-forming additive in the electrolyte is 0.1%, 0.2%, 0.3%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1% or any range consisting of any two of them.

[0066] In some embodiments, the separator may be a polypropylene separator, a polyethylene separator, or a composite separator composed of polyethylene and polypropylene.

[0067] The embodiment of the present application further provides an electric device, comprising the above-mentioned secondary battery. The secondary battery serves as a power supply for the electric device.

[0068] In some embodiments, the electrical equipment of the present application includes, but is not limited to: backup power supplies, motors, electric vehicles, electric motorcycles, power-assisted bicycles, bicycles, power tools, large household batteries, etc.

[0069] Embodiment 1:

[0070] Preparation of negative electrode materials:

[0071] The third substance, boric acid, and the second substance, catechol, are dispersed in deionized water and stirred until uniformly dispersed to obtain a first slurry, wherein the mass ratio of boric acid to catechol is 1:6.

[0072] Add active material silicon dioxide (Dv50: 6 um) to the first slurry, and continue stirring for 1 to 2 hours to obtain a second slurry, in which the mass ratio of the active material to boric acid is 1000:1.

[0073] The first substance, polyethyleneimine (molecular weight 10000Da), was added to the second slurry, and stirring was continued for 3 to 5 hours to obtain a third slurry, in which the mass ratio of polyethyleneimine to boric acid was 3:1.

[0074] The third slurry was transferred to a spray dryer and spray-dried under an argon atmosphere to obtain a silicon-based negative electrode active material.

[0075] Examples 2 to 4: The preparation method is the same as that of Example 1, except that the amounts of the first substance, the second substance and the third substance are adjusted. The specific parameters are shown in Table 1.

[0076] Example 5: The preparation method is the same as that of Example 1, except that the third substance, boric acid, is replaced by 1,4-phenylenediboric acid. Specific parameters are shown in Table 1.

[0077] Example 6: The preparation method is the same as that of Example 4, except that the second substance catechol is replaced by tannic acid. Specific parameters are shown in Table 1.

[0078] Example 7: The preparation method is the same as that of Example 4, except that the second substance catechol is replaced by gallic acid. The specific parameters are shown in Table 1.

[0079] Example 8: The preparation method is the same as that of Example 4, except that the molecular weight of the first substance polyethyleneimine is adjusted to 20,000 Da. Specific parameters are shown in Table 1.

[0080] Example 9: The preparation method is the same as that of Example 1, except that the third substance, boric acid, is replaced by phenylboric acid.

[0081] Example 10: The preparation method is the same as that of Example 1, except that the molecular weight of the first substance polyethyleneimine is adjusted, and the mass ratio among the first substance, the second substance and the third substance is adjusted. The specific parameters are shown in Table 1.

[0082] Example 11: The preparation method is the same as that of Example 1, except that the molecular weight of the first substance polyethyleneimine is adjusted, and the mass ratio among the first substance, the second substance and the third substance is adjusted. The specific parameters are shown in Table 1.

[0083] Example 12: The preparation method is the same as that of Example 1, except that the third substance, boric acid, is not added. The specific preparation method is as follows:

[0084] The second substance, catechol, is dispersed in deionized water and stirred until uniformly dispersed to obtain a first slurry.

[0085] Add active material silicon oxide to the first slurry, continue stirring for 1 to 2 hours to obtain a second slurry, wherein the mass ratio of the active material to catechol is 1000:6.

[0086] The first substance, polyethyleneimine (molecular weight 10000Da), was added to the second slurry, and stirring was continued for 3 to 5 hours to obtain a third slurry, wherein the mass ratio of polyethyleneimine to catechol was 3:6.

[0087] The third slurry was transferred to a spray dryer and spray-dried under an argon atmosphere to obtain a silicon-based negative electrode active material.

[0088] Comparative Example 1: The preparation method is the same as that of Example 1, except that catechol is replaced by phenol. Specific parameters are shown in Table 1.

[0089] Comparative Example 2: The preparation method is the same as that of Example 1, except that the first substance is replaced by polyethylene with a molecular weight of 10000 Da. The specific parameters are shown in Table 1.

[0090] Button battery production:

[0091] Prepare the negative electrode sheet. The negative electrode material, carbon black and binder polyacrylic acid (PAA) prepared in Examples 1 to 12 or Comparative Examples 1 to 2 are mixed in a weight ratio of 70:15:15 and dispersed in deionized water to form a uniform slurry. The slurry is then cast on a copper foil (thickness of 9 μm) by a doctor blade method and dried at 70°C. Cold pressing, trimming, and cutting are performed, and then dried at 100°C under vacuum for 12 hours to obtain a negative electrode sheet.

[0092] A 2025 button half-cell was assembled in a glove box filled with inert gas, where the contents of H2O and O2 were both less than 0.1 ppm. A metal lithium sheet was used as the counter electrode, PP / PE was used as the separator, and 1M LiPF6 (EC:DEC:DMC=1:1:1 vol%) + 8% FEC (fluoroethylene carbonate) was used as the electrolyte.

[0093] Performance Testing:

[0094] Cyclic performance test

[0095] Take 3 batteries from each group prepared as above, and repeatedly charge and discharge the batteries through the following steps, and calculate the discharge capacity retention rate of the batteries.

[0096] First, in a 25°C environment, discharge to 5mV at 0.5C, 5mV at 0.05C, 5mV at 0.02C, 5mV at 0.01C, and then charge to 1.5V at 0.1C, and record the discharge capacity and charge capacity of the first cycle. Then perform 50 discharge and charge cycles, and record the charge capacity of each cycle. According to the following formula:

[0097] First coulombic efficiency (%) = first cycle charge specific capacity / first cycle discharge specific capacity * 100

[0098] Cycle capacity retention rate (%) = 50th cycle capacity / first cycle capacity * 100

[0099] The initial coulombic efficiency and the average capacity retention rate after cycling of each group of batteries were calculated, as shown in Table 2.

[0100] Thickness expansion rate test of negative electrode full embedding state

[0101] Measure the thickness of the negative electrode before assembling the battery, record it as D0. Discharge the assembled battery at 0.1C to 5mV and then 0.02C to 5mV in a 25℃ environment, so that the negative electrode is in a fully embedded state. Disassemble the battery and test the thickness of the negative electrode in the fully embedded state, record it as D1. According to the following formula:

[0102] Thickness expansion rate (%) = (D1-D0) / D0*100

[0103] The thickness expansion rate of the negative electrode sheet when fully embedded is calculated, as shown in Table 2.

[0104] Table 1

[0105]

[0106]

[0107] Table 2

[0108]

[0109] As can be seen from Table 2, the present application provides a coating layer on the surface of the silicon-based material, and the coating layer has a self-repairing function, which helps to reduce the volume effect caused by the expansion of the active material, and its self-repairing property gives the active material a better fatigue resistance. The coating layer also helps to inhibit the side reaction between the silicon-based material and the electrolyte, thereby helping to improve the long-term cycle stability of the material.

[0110] Comparing Examples 1-8 with Comparative Examples 1-2, under the same conditions, Comparative Examples 1 and 2 cannot form an effective polymer coating layer because the first substance or the second substance has only a single reactive functional group, and therefore cannot effectively inhibit volume expansion.

[0111] It can be seen from Examples 1-8 and Example 12 that the introduction of boric acid into the polymer to form a coating layer with reversible borate ester bonds can increase the fatigue resistance of the polymer and thus improve the cycle life of the battery.

[0112] It can be seen from Examples 1-8 and Example 9 that when the third substance phenylboronic acid has a single reactive group, a polymer coating layer having a reversible borate ester bond cannot be formed, and thus the ability to inhibit volume expansion becomes poor.

[0113] From the results of Examples 1 to 12 of the present application and Comparative Example 2, it can be found that when polyethyleneimine is replaced by polyethylene, since polyethylene cannot form hydrogen bonds, π-π interactions, and BN coordination between catechol and boric acid, the self-healing property of the polymer coating is poor, resulting in poor long-term cycle performance of the material.

[0114] From the results of Examples 1-9 and 10 of the present application, it can be seen that the coating thickness is 40nm, which is less than 100nm. When the coating thickness is too thin, the coating is uneven, it is difficult to form a complete coating, the silicon-based material expansion inhibition effect is poor, the side reaction between the active material and the electrolyte is serious, and the cycle attenuation is serious. From the results of Examples 1-9 and 11, it can be seen that the coating thickness of Example 11 is 1210nm, which exceeds 900nm. When the coating is too thick, the specific capacity of the silicon-based active material is reduced, and the impedance of lithium ions penetrating the coating increases, polarization is serious, and the capacity decays quickly.

[0115] In the above embodiments, the description of each embodiment has its own emphasis. For parts that are not described in detail in a certain embodiment, reference can be made to the relevant descriptions of other embodiments.

[0116] The above is a detailed introduction to a negative electrode material, a preparation method, a secondary battery and an electrical device provided in the embodiments of the present application. Specific examples are used in this article to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the method of the present application and its core idea; at the same time, for technical personnel in this field, according to the idea of ​​the present application, there will be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as a limitation on the present application.

Claims

1. A negative electrode material, characterized in that: The invention comprises an active material and a coating layer coated on the surface of the active material, wherein the coating layer comprises a first substance, the first substance has a primary amino group; at least part of the primary amino group is connected to a second substance through a covalent bond; The first substance includes polyethyleneimine; The second substance has a catechol group, the catechol group is at least partially connected to a third substance, and the third substance includes one or more of 1,4-phenylenediboronic acid, 1,3-phenylenediboronic acid and boric acid; The active material includes one or more of silicon element, silicon-carbon compound, silicon-oxygen compound, silicon-nitrogen compound and silicon alloy.

2. The negative electrode material according to claim 1, characterized in that The second substance includes one or more of catechol, gallic acid, tannic acid, quercetin, ellagic acid, chlorogenic acid, protocatechuic acid and epicatechin gallate.

3. The negative electrode material according to claim 1, characterized in that The mass ratio of the coating layer to the active material is 1:(40-200); and / or, The particle size of the active material is 100 nm to 20 μm; and / or, The coating layer has a thickness of 100 nm to 900 nm; and / or, The molecular weight of the first substance is 8000-20000 Da.

4. The negative electrode material according to claim 1, characterized in that The mass ratio of the first substance to the second substance is (2-15):(2-10).

5. The negative electrode material according to claim 1, characterized in that The mass ratio of the first substance, the second substance and the third substance is (2-15):(2-10):

1.

6. A method for preparing a negative electrode material as claimed in claim 1, characterized in that: The following steps are involved: dispersing the second substance in a solvent to obtain a first slurry; adding the active material to the first slurry to obtain a second slurry; adding the first substance to the second slurry to obtain a third slurry; The third slurry is spray-dried under an inert atmosphere to obtain the negative electrode material; Wherein, the first substance comprises polyethyleneimine; The second substance has a catechol group, the catechol group is at least partially connected to a third substance, and the third substance includes one or more of 1,4-phenylenediboronic acid, 1,3-phenylenediboronic acid and boric acid; The active material includes one or more of silicon element, silicon-carbon compound, silicon-oxygen compound, silicon-nitrogen compound and silicon alloy.

7. A secondary battery, characterized in that: It comprises a negative electrode plate, wherein the negative electrode plate comprises the negative electrode material as described in any one of claims 1 to 5 or the negative electrode material prepared by the method for preparing the negative electrode material as described in claim 6.

8. An electrical device, characterized in that: Comprising the secondary battery as claimed in claim 7.

Citation Information

Patent Citations

  • Negative electrode active material for lithium ion secondary battery, lithium ion secondary battery negative electrode arranged by use thereof, and lithium ion secondary battery arranged by use thereof

    JP2017183051A